Extracellular vesicles derived from Akkermansia muciniphila promote placentation and mitigate preeclampsia in a mouse model - Yun Chen; Zihao Ou; Menglan Pang; Zixin Tao; Xifen Zheng; Zhipeng Huang; Dongni Wen; Qianbei Li; Ruisi Zhou; Peng Chen; Bo Situ; Chao Sheng; et al. (Journal of Extracellular Vesicles, 2023)
Abstract Preeclampsia (PE) is a multisystem disorder with high maternal morbidity and mortality rates. Currently, no practical therapeutic approach is available to prevent PE progression, except for early delivery. Gut dysbiosis is associated with PE development. Previous data showed that the abundance of Akkermansia muciniphila (Am) was lower in patients with PE than in normotensive pregnant women. Here, in this study, decreased abundance of Am was observed in a PE mouse model. Also, we found that administration with Am could significantly attenuate systolic blood pressure, promote foetal growth and improve the placental pathology in mice with PE. Moreover, Am‐derived extracellular vesicles (AmEVs) were transferred from the gastrointestinal (GI) tract to the placenta and mitigated pre‐eclamptic symptoms in PE mice. These beneficial effects of AmEVs were mediated by enhanced trophoblast invasion of the spiral artery (SpA) and SpA remodelling through activation of the epidermal growth factor receptor (EGFR)–phosphatidylinositol‐3‐kinase (PI3K)–protein kinase B (AKT) signalling pathway. Collectively, our findings revealed the potential benefit of using AmEVs for PE treatment and highlighted important host–microbiota interactions.